2022
DOI: 10.3390/foods11142124
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Diet-Supplemented and Endogenously Produced Omega-3 Fatty Acids against HFD-Induced Colon Inflammation in Mice

Abstract: Perilla (Perilla frutescens) oil reduces high-fat-diet-induced colon inflammation by suppressing the NF-κB pathway. In the current study, we compared the effect of endogenously produced and externally supplemented omega-3 fatty acids on high-fat-diet-induced colon inflammation. The fat-1 transgenic mice that endogenously synthesize omega-3 fatty acids were backcrossed with C57BL/6J wild-type mice to obtain transgenic (TR) and wild-type (WT) littermates. Five-week-old male littermates were divided into five gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…Natural oils have a protective effect on the intestinal barrier. Supplementation with perilla oil has been found to significantly improve goblet cells that have been damaged by DSS, protect the integrity of the gut epithelium, and increase the expression levels of markers of epithelial barrier integrity, such as Claudin-1, Zo-1, Muc1, and Muc3, as shown by western blot analysis in colonic tissue [52]. Walnut oil also has a protective effect on intestinal barrier function.…”
Section: Protecting the Intestinal Barriermentioning
confidence: 90%
See 2 more Smart Citations
“…Natural oils have a protective effect on the intestinal barrier. Supplementation with perilla oil has been found to significantly improve goblet cells that have been damaged by DSS, protect the integrity of the gut epithelium, and increase the expression levels of markers of epithelial barrier integrity, such as Claudin-1, Zo-1, Muc1, and Muc3, as shown by western blot analysis in colonic tissue [52]. Walnut oil also has a protective effect on intestinal barrier function.…”
Section: Protecting the Intestinal Barriermentioning
confidence: 90%
“…Further exploration has found that Perilla oil can alleviate colonic inflammation by inhibiting the activation of NF-κB in the colon of mice [51]. Another study found that Perilla oil can reduce colonic inflammation in mice by protecting the intestinal barrier function, inhibiting the NF-κB pathway, and reducing the expression of pro-inflammatory genes, which may be related to the activation of GPR120 [52]. For the DSS-induced colitis model, Perilla oil also has an improving effect.…”
Section: Perilla Oilmentioning
confidence: 99%
See 1 more Smart Citation
“…The supplementation with n-3 fatty acids in the diet has been reported to significantly attenuate HFD-induced colon inflammation in mice. 56 Both polyunsaturated fatty acids produce either anti-inflammatory or proinflammatory metabolites, and overall, oxidized lipids derived from n-6 PUFAs exhibit more potent pro-inflammatory and pro-proliferative properties compared to those originating from n-3 PUFAs. 57−60 Based on this, we hypothesized that Rk3 may reverse HFD-induced colon inflammation by modulating the content and metabolic level of n-6 fatty acids.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Omega-3 polyunsaturated fatty acids are a general term that includes alpha-linolenic acid, which is abundant in perilla oil (PO) [64]. This omega-3 polyunsaturated fatty acid has been proven to be associated with antiinflammatory [65] and lipid metabolism disorders [66]. The intake of such dietary fatty acids can improve the intestinal flora [67] as well as intestinal inflammation and metabolic disorders in diabetic patients [68].…”
Section: Fatty Acids Tocopherols and Phytosterolsmentioning
confidence: 99%